Hubungan Antara Efikasi Diri Akademik dan Kesejahteraan Psikologis Pada Mahasiswa Universitas Negeri Malang - Kuserawati, Selvia; Farida, Ika Andrini (Universitas Negeri Malang, 2022)
Abstract: Psychological well-being becomes an important factor for college students to carry out their taskand responsibility to achieve success at university. Compare to the previous research which showsa positive correlation between self-efficacy and psychological well-being of high school students ingeneral way, this study focused on academic self-efficacy in college students which aimed todiscover the correlation between academic self-efficacy and psychological well-being of the MalangState University’s students. The sampling technique used is cluster sampling with a total sample of259 students from the Faculty of Mathematics and Natural Sciences, Faculty of Engineering, andFaculty of Psychology at the State University of Malang. The Academic Self-Efficacy (TASES) andpsychological well-being are used to collect the data. The methodes used are descriptive andcorrelational analysis. The results of this study indicate 67,2% of the Malang State University’sstudents have a high level of academic self-efficacy and 55,6% of them have a high level ofpsychological well-being. The results of correlation test showed a coefficient of 0,643 which meansthat there is a significant positive correlation between academic self-efficacy and psychologicalwell-being in Malang State University’s students. Through this research, it’s hoped that the MalangState University’s Students can improve their academic self-efficacy to achieve better psychologicalwell-being Abstrak: Kesejahteraan psikologis menjadi faktor penting bagi mahasiswa dalam melaksanakan tugas dantanggung jawab untuk mencapai kesuksesan di universitas. Temuan penelitian terdahulumenunjukkan bahwa ada hubungan positif efikasi diri dengan kesejahteraan psikologis pada siswasekolah menengah atas. Penelitian terdahulu cenderung meneliti efikasi diri secara umum padasiswa sedangkan penelitian ini berfokus pada efikasi diri akademik pada mahasiswa yang bertujuanuntuk mengetahui hubungan antara efikasi diri akademik dan kesejahteraan psikologis padamahasiswa Universitas Negeri Malang. Teknik sampling yang digunakan adalah cluster samplingdengan jumlah sampel sebesar 259 mahasiswa yang berasal dari Fakultas MIPA, Fakultas Teknik,dan Fakultas Psikologi Universitas Negeri Malang. Pengumpulan data menggunakan adaptasi dariThe Academic Self-Efficacy Scale (TASES) dan skala kesejahteraan psikologis. Analisis data yangdigunakan adalah analisis deskriptif dan korelasional. Hasil penelitian ini menunjukkan sebanyak67,2% mahasiswa Universitas Negeri Malang memiliki tingkat efikasi diri akademik yang tinggi dansebanyak 55,6% mahasiswa Universitas Negeri Malang memiliki tingkat kesejahteraan psikologisyang tinggi. Hasil uji korelasi menunjukkan koefisien sebesar 0,643 yang berarti ada hubunganpositif yang signifikan antara efikasi diri akademik dan kesejahteraan psikologis pada mahasiswaUniversitas Negeri Malang. Melalui penelitian ini diharapkan mahasiswa Universitas Negeri Malangdapat meningkatkan efikasi diri akademik untuk mencapai kondisi kesejahetraan psikologis yanglebih baik.